Analytical calculation of magnetic field of bearingless flux‐switching permanent‐magnet machine based on doubly‐salient relative permeance method. Issue 5 (25th February 2020) - Zhou, Yangzhong; Wu, Xin
Abstract : A doubly‐salient relative permeance method is presented herein to predict the magnetic field of bearingless flux‐switching permanent‐magnet machines (BFSPMMs). Firstly, the subdomain model method is used to compute the magnetic field of slotless BFSPMMs. Then, the slotting effect of the stator and rotor is obtained by the doubly‐salient relative permeance method. By combining the two above, the air‐gap magnetic field of slotted BFSPMMs can be obtained. The doubly‐salient relative permeance method is based on the theory of the subdomain model method. The whole doubly‐salient structure is divided into several subdomains, and the Laplace equations for subdomains are established. Then, according to the boundary conditions between subdomains and the core, and the continuity conditions between adjacent subdomains, the equations are solved to calculate the slotting effect. Based on the proposed analytical model, the flux density and electromagnetic performances including back‐electromotive force (EMF), torque, and suspension force are predicted and compared with the finite element method results. Furthermore, the back‐EMF of the prototype motor is measured and the suspension experiments are carried out based on the analytical method. The comparison results and experiment results verify the validity of the analytical method.